Upaya Meningkatkan Kreativitas Figural Melalui Kegiatan Menggambar pada Anak Kelompok B TK Dharma Wanita II Kedu Kecamatan Kedu Kabupaten Temanggung Semester II Tahun Pelajaran 2017/2018 - Wahju Wahju (Universitas PGRI Semarang, 2020)
Figural creativity is the ability to come up with new ideas or ideas through the images created. This figural creativity is based on drawing activities to generate new ideas or ideas, but does not require drawing skills or abilities. This research was conducted because of the low figural creativity of Group B children TK Dharma Wanita II Kedu. The objectives of this study were: 1) to describe the figural creativity of Group B TK Dharma Wanita II Kedu, Kedu District, Temanggung District, Semester II, Academic Year 2017/2018 after being given the action of drawing activities, 2) to determine the magnitude of the increase in figural creativity through drawing activities in children Group B TK Dharma Wanita II Kedu, Kedu District, Temanggung Regency, Semester II, 2017/2018 Academic Year. The subjects of this study were 16 students of Group B TK Dharma Wanita II Kedu totaling 16 children. The research was conducted from April to May 2018. The data collection methods used were observation, documentation and interviews. Based on the results of research and discussion, it can be concluded that drawing activities carried out through drawing with colored pencils, crayons and watercolor media can increase the figural creativity of Group B children TK Dharma Wanita II Kedu Temanggung Semester II 2017/2018 Academic Year. This creativity is indicated by the achievement of good assessment criteria before the action of 18.75%, increasing to 43.75% in Cycle I, and increasing to 81.25% in Cycle II. This research is in accordance with the expected indicators of success which is characterized by the child being able to produce different images and being able to develop ideas through an explanation of the results of the pictures.